STUDI KASUS PENATALAKSANAAN FISIOTERAPI PADA REHABILITASI FASE 1 PASIEN PASCA REKONSTRUKSI ACL DAN MENISCUS REPAIR - Rizal, Yose; Marzuki, Toto; Mariza, Amelia Dwi (Journal of Physical Activity and Sports (JPAS), 2025)
Anterior cruciate ligament (ACL) and meniscus injuries are common knee injuries in athletes that require comprehensive postoperative rehabilitation. This study aimed to determine the effectiveness of a physiotherapy program combining electrotherapy modalities (TENS, NMES, Ultrasound) and muscle contraction exercises during phase 1 rehabilitation after ACL reconstruction and meniscus repair. A case study with a pre- and post-test design was conducted on a 22-year-old male soccer player who underwent physiotherapy for two weeks (June 16–30, 2025) at Fisiohands Clinic, Pekanbaru. Evaluations were performed using the Visual Analog Scale (VAS) for pain, a goniometer for range of motion (ROM), and the Lower Extremity Functional Scale (LEFS) for knee function. The results showed a reduction in resting pain from 6/10 to 3/10 and movement pain from 8/10 to 5/10. Knee ROM improved from S=0°–16°–68° to S=0°–8°–94°, while the LEFS score increased from 27 to 38. In conclusion, the combination of electrotherapy and muscle contraction exercises was effective in reducing pain, improving ROM, and enhancing knee function in the early rehabilitation phase after ACL reconstruction and meniscus repair, although the patient remained in the category of major functional limitations.